A Proposed Program for the Audit of Municipal Lands in Accordance with International Auditing Standards and INTOSAI Standards - Alaa Mohammed Saeed Ahmed; Khawla Hussein Hamdan (Journal of Madenat Alelem University College, 2021)
The research aims to prepare a proposed program in accordance with auditing standards and international standards of INTOSAI and based on the laws and regulations and instructions in force and that the auditor to take into account when checking the territory of the municipalities to contribute to the improvement of the process of auditing the territory of the municipalities and assist auditors in completing audits of high underbody procedures and achieve audit efficiency and effectiveness of the goals, and will be reflected to give an opinion on the fairness of the financial statements of municipal institutionsResearch concluded that the Federal Office of financial supervision approved program of activity auditing the municipalities did not include a detailed audit procedures for the territory of the municipalities did my Consider international standards and INTOSAI standards, so researchers recommend the adoption of the proposed program.